Protocol for qRT-PCR analysis from formalin fixed paraffin embedded tissue sections from diffuse large b-cell lymphoma: Validation of the six-gene predictor score - Tekin, Nilgun (2016)
As a part of an international study on the molecular analysis of Diffuse Large B-cell Lymphoma (DLBCL), a robust protocol for gene expression analysis from RNA extraction to qRT-PCR using Formalin Fixed Paraffin Embedded tissues was developed. Here a study was conducted to define a strategy to validate the previously reported 6-gene (LMO2, BCL6, FN1, CCND2, SCYA3 and BCL2) model as predictor of prognosis in DLBCL. To avoid variation, all samples were tested in a single centre and single platform. This study comprised 8 countries (Brazil, Chile, Hungary, India, Philippines, S. Korea, Thailand and Turkey). Using the Kaplan-Meier and log rank test on patients (n=162) and two mortality risk groups (with those above and below the mean representing high and low risk groups) confirmed that the 6-gene predictor score correlates significantly with overall survival (OS, p < 0.01) but not with event free survival (EFS, p=0.18). Adding the International Prognostic Index (IPI) shows that the 6-gene predictor score correlates significantly with high IPI scores for OS (p < 0.05), whereas those with low IPI scores show a trend not reaching significance (p=0.08). This study defined an effective and economical qRT-PCR strategy and validated the 6-gene score as a predictor of OS in an international setting.